Reduced CX3CL1 Secretion Contributes to the Susceptibility of Oral Leukoplakia-Associated Fibroblasts to Candida albicans - Cheng, Ran; Li, Duo; Shi, Xueke; Gao, Qinghong; Wei, Changlei; Li, Xiaoyu; Li, Yan; Zhou, Hongmei (Frontiers in Cellular and Infection Microbiology, 2016)
Candida leukoplakia (OLK) is a kind of oral leukoplakia combined with chronic candidal infection, which plays an important role in the malignant transformation of OLK. However, little is known about the etiology, including susceptibility of leukoplakia to candidal adhesion, invasion and infection. Some antimicrobial peptides secreted by oral epithelial cells or fibroblasts potentially have antifungal activities against Candida albicans (C. albicans). In this study, we established three co-culture models to simulate different C. albicans-fibroblasts interactions during progression of candida leukoplakia. The susceptibility of oral leukoplakia-associated fibroblasts (LKAFs) to C. albicans and its underlying mechanism were determined. Samples of 14 LKAFs and 10 normal fibroblasts (NFs) were collected. The co-culture models showed that LKAFs had promoted the adhesion, invasion, and survival of C. albicans compared with NFs. CX3CL1, a chemokine with antifungal activity, was less abundant in LKAFs than NFs. Overexpression of CX3CL1 via transfection in LKAFs could partly restore the resistance to C. albicans. We also showed that inhibition of ERK could suppress CX3CL1 secretion. While phosphor-ERK was inhibited in LKAFs compared with NFs. Besides, the expression of a shedding enzyme for CX3CL1, disintegrin and metalloproteinase domain (ADAM) 17 was decreased in LKAFs than NFs. In conclusion, LKAFs produced and secreted less CX3CL1 by inhibiting the ERK signaling pathway, thereby contributing to impaired cell resistance to C. albicans.